AMBIGUITY IN SONG LYRICS OF "WILDFLOWER" BY Billie Eilish: A SEMANTIC ANALYSIS - IMAS MEILISA DEWIWORO PRATIWI Dewi (MEMACE: Jurnal Linguistik, Pendidikan Bahasa Indonesia, dan Asing, 2025)
Song lyrics represent a unique form of literary discourse in which language is employed not only to convey information but also to evoke emotions, construct imagery, and encourage multiple interpretations. One linguistic phenomenon frequently found in song lyrics is ambiguity, which allows listeners to derive different meanings from the same linguistic expression. This study investigates ambiguity in the lyrics of "Wildflower" by Billie Eilish using a semantic approach. The objectives of this research are to identify the types of ambiguity occurring in the song lyrics and to explain how ambiguity contributes to the construction of meaning within the song. This study employs a qualitative descriptive method. The data consist of words, phrases, and clauses identified as ambiguous in the lyrics. Data were collected through documentation and close-reading techniques and analyzed using semantic theories of ambiguity proposed by Ullmann, Kreidler, and Leech. The findings indicate that both lexical ambiguity and structural ambiguity are present in the lyrics. Lexical ambiguity appears in several key lexical items that possess multiple semantic interpretations, while structural ambiguity emerges from syntactic constructions that permit more than one meaning. The analysis demonstrates that ambiguity functions as an artistic and communicative device, enabling listeners to interpret the song from various emotional, psychological, and interpersonal perspectives. Furthermore, ambiguity contributes significantly to the aesthetic quality of the lyrics and reinforces the themes of guilt, memory, emotional conflict, and self-reflection that characterize the song. The study concludes that ambiguity serves as an essential stylistic feature in contemporary song lyrics and enriches the communicative potential of musical discourse